Pengaruh Sektor Pariwisata Terhadap Pertumbuhan Ekonomi di Kabupaten Banyumas - Anggun Sepfiana; Faizal Rizky Yuttama (ManBiz: Journal of Management and Business, 2025)
This research seeks to assess how tourism product characteristics affect destination value, how the image of a destination impacts destination value, and how destination value relates to intentions of loyalty. A quantitative approach and multiple regression analysis were applied in the study. The findings reveal that the C.R value is 0.623 < 1.967 and the p-value is 0.54 > 0.001, leading to the acceptance of H0. This shows that tourism product characteristics do not positively affect destination value. The C.R value is 1.842 < 1.967 and 0.066 > 0.001, resulting in the acceptance of H0. This suggests that the image of a destination does not positively influence destination value either. However, the C.R value is 14.207 > 1.967 and the p-value < 0.001, which means H0 is rejected. This indicates a positive effect of destination value on intentions of loyalty.